APPLICATION OF BIOMASS FLY ASH AS A POZZOLANIC MATERIAL FOR STABILIZATION OF LOW-SWELLING CLAY - R. Rachan; W. Chim-oye; S. Horpibulsuk (International Association of Lowland Technology, 2009)
The present paper investigates the possibility of utilizing biomass fly ash to partially replace Type I Portland cement for stabilization of a low-swelling clay. It is found that the fly ash can be used as a pozzolanic material. The 10% replacement ratio is an effective ratio where the input of fly ash is sufficient for secondary reaction. The influential parameter controlling the strength development of blended cement is clay-water/cement ratio, wc/C. The cement content of the blended cement is the summation of the input of cement, Ci and the equivalent cement, Ce. The Ce is determined based on the concept of an efficiency factor (k), which is adopted as a measure of the relative performance of supplementary cementing material compared with Type I Portland cement. The Ce is equivalent to kF where F is fly ash content and k is efficiency factor. From the analysis, the value of k is dependent upon the replacement ratio and curing time, and irrespective of binder content and water content. A phenomenological model for assessing the strength development is introduced and verified. It can possibly be applied as a simple and rational tool for predicting the strength development of other blended cement stabilized low swelling clays.